Dinâmicas competitivas no setor da saúde: um estudo em instituições hospitalares filantrópicas de Porto Alegre - Prestes, Elvis Preslli (Universidade do Vale do Rio dos Sinos, 2012)
In a globalized business environment, wich is constantly changing, hospitals organizations have been evolving and adapting to the demands imposed on them, either by the government, through public health policies or by the market, through the natural pressure for efficiency and effectiveness, and the pursuit of economic sustainability. When approaching the theme of competitive dynamics in the health section within the philanthropic hospital organizations from the city of Porto Alegre, the present study investigates the transformation and strategic movements that occur in the institutions. The financial difficulties faced by most Brazilian philanthropic hospital health care organizations, which are those with a special tax exemption, have been raising concerns of political and social order and has become, in recent years, one of the biggest challenges faced by the entities already mentioned. The choice of the theme is justified by the fact that the health sector has capital importance, for any society's welfare, not only by the nature of its operations, but also for fostering scientific and technological development. The aim of this study consisted in answering the following question: what are the competitive dynamics that are currently displayed in the environment of the philanthropic health instutions in Porto Alegre? The chosen method had a qualitative character from an exploratory case study. In order to do this, six directors of health care reference entities from Porto Alegre were interviewed, the Secretary of Health of city, two former Secretaries of Health of Rio Grande do Sul, a former National Secretary of Health, two directors of professional associations, the superintendent of an operator of health security plan, three representatives of the supply chain health, and a representative of imaging services and diagnosis. It was applied a semi-structured questionnaire, directed to each category of respondent, covering issues like the regulatory environment in the healthcare segment, the implications of sustainability for different entities, the strategies adopted in the sector, the pressures imposed by the forces that govern the competition, and elements regarding the value proposition to medical services. The interviews were taped and transcribed, and proceed to content analysis, as analysis method and data interpretation. The results indicate the adoption of distinguished strategies by the surveyed entities, highlighting the cooperation as prevailing strategic orientation, the value proposition as a way of positioning, horizontalization of the health institutions and focus on high complexity specialties. The regulatory environment of the sector, as well as its geographical localization and organizational vessel are presented as elements that subject the contents of the surveyed hospital entities' answers.
Keywords: Estratégias; Gestão hospitalar; Organizações hospitalares; Proposição de valor; Strategies; Hospital management; Health services; Hospital organizations; Value proposition; ACCNPQ::Ciências Sociais Aplicadas::Administração